Analisis Peran Teknologi IoT dalam Praktik Regeneratif Soil Management: Studi Kualitatif atas Best Practices Global - Aryanti Aryanti; Raditya Ahnaf Fauzan; Siti Wahidatul Atsna; Chairunnissa Putri; Tazkia Nurul; Yeni Budiawati (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
This qualitative study analyzes the role of Internet of Things (IoT) technology in regenerative soil management practices, focusing on global best practices that can be replicated in Indonesia. As a vital resource, soil plays a crucial role in supporting agricultural productivity and food security, yet it faces significant threats from degradation due to unsustainable agricultural practices and chemical overuse. The study emphasizes the importance of integrating IoT technology to monitor and manage soil conditions in real-time, enhancing decision-making for sustainable agriculture. Key questions addressed include how IoT supports regenerative practices, examples of successful global implementations, and the effectiveness of IoT in improving soil quality and organic carbon content. Findings highlight that IoT can significantly enhance soil health by enabling precise monitoring of key parameters such as moisture, pH, and temperature, thereby facilitating timely interventions. The research also explores the challenges and opportunities associated with IoT adoption in regenerative agriculture, particularly in developing countries. Ultimately, the integration of IoT in regenerative soil management presents a promising pathway to achieving sustainable agricultural practices that meet the growing global food demands while restoring ecosystem health.